The Crimean Campaign with "The Connaught Rangers" : 1854-55-56. - Steevens, Nathaniel (Andrews UK, 2012)
The events described in this book come from the pages of the author's own letters and diary, written during the campaign in which he was present throughout. It is a record of his impressions and observations, written at the time without any thought of publication; it was at the request of several friends that the book got published - and a remarkably detailed record it is. The regiment embarked for the Crimea on 4th April 1854, less than two weeks after the declaration of war, with a strengt ...